Association of Irreversible Pulpitis and Multi Visit Root Canal Treatment. - G, NIVETHA; K, ANJANEYULU; S, ARVIND (The journal of contemporary issues in business and government, 2021)
Irreversible pulpitis is a persistent inflammatory condition of pulp caused by noxious stimuli. It may be symptomatic or asymptomatic. Multi visit root canal treatment is safer and commonly used method which is given 2 to 3 appointments and this method reduces error and infection. The aim of this study is to find out the association of multi root canal treatment in irreversible pulpitis patients visiting Saveetha Dental College. A retrospective study was carried out in University in Chennai between July 2019-March 2020.The data were collected from patients records analysed from the data of 86000 patients between June 2019-March 2020 . The data were entered in an Excel sheet and subjected to statistical analysis using SPSS software.A chi square test was done between age and gender, age and number of visits,gender and number of visits and teeth number and number of visits. The results were formulated in tables and graphs. The results showed that a total of 5366 patients were diagnosed with irreversible pulpitis of which 3037 patients underwent multi visit root canal treatment. .The study concludes that mandibular first molars were highly affected with irreversible pulpitis and underwent multi root canal treatment .